2005
DOI: 10.1016/j.femsle.2005.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification ofBifidobacterium lactisLAFTI�B94 in human faecal samples from a consumption trial

Abstract: A method was developed to allow detection of the probiotic Bifidobacterium lactis LAFTI B94 in human clinical samples. A new probe, Laf94p, was developed to accomplish colony hybridization of B. lactis B94. PCR detection of B94 was also achieved using the species-specific (B. lactis) primer pair. These tests and probes allowed detection and quantification of B94 in the human intestinal flora. The sensitivity of the probe was assessed by monitoring faecal levels of B94 in humans who were fed the culture. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…The rapid disappearance of Bb-12 from fecal samples following cessation of feeding is consistent with other published clinical studies (7,22). Some studies have seen persistence in one or two subjects for a week or two longer (42). However, this may have been due to variations in subject reliability or to inadvertent consumption of other foods containing bifidobacteria rather than persistence of the species.…”
Section: Discussionsupporting
confidence: 87%
“…The rapid disappearance of Bb-12 from fecal samples following cessation of feeding is consistent with other published clinical studies (7,22). Some studies have seen persistence in one or two subjects for a week or two longer (42). However, this may have been due to variations in subject reliability or to inadvertent consumption of other foods containing bifidobacteria rather than persistence of the species.…”
Section: Discussionsupporting
confidence: 87%
“…The prolonged exposure of this subspecies to dairy fermentation environments is further supported by the reduced size of the genomes of this subspecies, which is a phenomenon that has been found to occur in organisms that are in less-complex environments where fewer features are needed to be successful, such as the genome reduction of Buchnera aphidicola, which is predicted to be due to environmental changes (230). This may explain the inability of these bacteria to persist in the intestines of human subjects, as they have been observed to disappear rapidly after stoppage of eating foods containing these bacteria (88,215,300,319).…”
Section: Genome Adaptation Of Intestinal Bifidobacteria To Environmenmentioning
confidence: 99%
“…Bifidobacterium animalis subsp. lactis Bb12 (Lake Foods, SA) was used as a reference strain because it has been a commercial strain for over 25 years and is cited in more than 200 scientific publications (Su et al, 2005;Barrangou et al, 2009;Buruleanu et al, 2012).…”
Section: Bacterial Isolatesmentioning
confidence: 99%
“…The MLSA approach is one of the best techniques that can be used for the phylogenetic analysis of strains of closely related species (Delétoile et al, 2010). Accuracy in probiotic strain identification is imperative during probiotic food product development as well as in clinical trials (Su et al, 2005). The MLSA approach was also applied in the present study because the precisely identified strains were intended to be included in a probiotic fermented maize beverage, in later work.…”
Section: Identification Based On Protein-coding Gene Sequencesmentioning
confidence: 99%
See 1 more Smart Citation